A social history of Christian origins - Joseph, Simon J., 1966- author.
1 online resource.
Keywords: "A Social History of Christian Origins explores how the theme of the Jewish rejection of Jesus - embedded in Paul's letters and the New Testament Gospels - represents the ethnic, social, cultural, and theological conflicts that facilitated the construction of Christian identity. Readers of this book will gain a thorough understanding of how a central theme of early Christianity - the Jewish rejection of Jesus - facilitated the emergence of Christian anti-Judaism as well as the complex and multi-faceted representations of Jesus in the Gospels of the New Testament. This study systematically analyses the theme of social rejection in the Jesus tradition by surveying its historical and chronological development. Employing the social-psychological study of social rejection, social identity theory, and social memory theory, Joseph sheds new light on the inter-relationships between myth, history, and memory in the study of Christian origins and the contemporary (re)construction of the historical Jesus. A Social History of Christian Origins is primarily intended for academic specialists and students in ancient history, biblical studies, New Testament studies, Religious Studies, Classics, as well as the general reader interested in the beginnings of Christianity"--